Estágio supervisionado obrigatório linfoma intestinal e mesentérico em cão: relato de caso. - Silva, Amanda Beatriz Bráz da (Universidade Federal Rural do Semi-Árido, 2021)
The present work describes the activities performed during the mandatory supervised internship, carried out at the Laboratory of Veterinary Microbiology of the Federal Rural University of Semi-Árido, located in the city of Mossoró - Rio Grande do Norte. The internship took place between the period of June 14th to August 6th, 2021, totaling 240 hours of work. During the period, activities related to the medical clinic for small animals and the area of veterinary microbiology were carried out, like aid during appointments, medication administration, collect of biological materials for analysis and production of reports, among others. During the internship, the clinical treatment of dogs and cats was followed up, where a dog diagnosed with intestinal and mesenteric lymphoma was chosen to prepare this case report. The patient was a male, mixed breed, weighing 12 kg, 7 years and 3 months old, neutered. After performing the anamnesis and physical examination, an abdominal neoplasm was suspected, and additional tests were requested. Ultrasonography found the presence of a mass in the small intestine, specifically in the jejunum, with involvement of the adjacent mesentery, suggestive for neoplasia. In face of this, it was discussed with the tutor the performing an exploratory laparotomy to assess the extension of the mass and involvement of the structures, for subsequent removal of the tumor, biopsy and histopathological analysis. During the surgical procedure, the presence of a focal mass in the final region of the jejunum was seen, with involvement and adherence of the adjacent mesentery. We opted for the excision of approximately 22 centimeters of the small intestine, being sent for pathology, having intestinal and mesenteric lymphoma as a report. As this is an oncological patient, chemotherapy was indicated, but the tutor chose not to do it, being treated and medicated during the post-surgery period, when the animal was released and is doing well so far. Thus, it is concluded that the mandatory supervised internship is a step with great importance for the training of the veterinarian. The follow-up of the clinical case brought important lessons, since intestinal lymphoma is a rare neoplasm in dogs, with rapid development and difficult diagnosis, which makes it a great challenge for the clinician and justifies the importance of this report for the oncology veterinary field.
Keywords: Neoplasia maligna; Laparotomia exploratória; Enterectomia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA